To solve the polynomial subtraction \((m^2 + 6m + [?]) - (2m^2 - [?]m + 1) = -m^2 + 9m + 4\), we need to fill in the blanks such that the equation holds true.
Let's denote \( a = ? \) and \( b = ? \) for convenience:
-
Start with the left-hand side of the equation: \[ (m^2 + 6m + a) - (2m^2 - bm + 1) \] This simplifies to: \[ m^2 + 6m + a - 2m^2 + bm - 1 = (-m^2 + (6 + b)m + (a - 1)) \]
-
Now, we want this expression to equal \(-m^2 + 9m + 4\): \[ -m^2 + (6 + b)m + (a - 1) = -m^2 + 9m + 4 \]
-
From this comparison, we can equate the coefficients:
-
For the \(m\) term: \[ 6 + b = 9 \] Solving for \(b\), we subtract 6 from both sides: \[ b = 9 - 6 = 3 \]
-
For the constant term: \[ a - 1 = 4 \] Solving for \(a\), we add 1 to both sides: \[ a = 4 + 1 = 5 \]
-
Now, we can fill in the blanks: \[ (m^2 + 6m + [5]) - (2m^2 - [3]m + 1) = -m^2 + 9m + 4 \]
Thus, the values to fill in the blanks are:
- The first blank: 5
- The second blank: 3
Final answer: \[ \text{Fill in the blanks with "5" and "3".} \]